Novacene: The coming age of hyperintelligence—James Lovelock’s vision of posthumanism - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
James Lovelock, who is famous for the Gaia hypothesis, has written a new book called Novacene: The Coming Age of Hyperintelligence. It is an extended argument about an impending new epoch on Earth called Novacene in which biological life as we know it will evolve into lifeforms based on cyber technology (i.e., cyborgs) built from non-biological materials. Novacene may be seen as a development of the ideas presented in Lovelock’s earlier book A Rough Guide to The Future. In Novacene, the Earth will be populated by cyborgs, which are self-replicating and self-improving mechanical systems that will eventually dominate and rule the Earth. These cyborgs will possess intelligence and knowledge beyond our understanding.